2010
DOI: 10.1007/s11606-010-1446-2
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Colonoscopy Services—Responsibilities of Referring Clinicians

Abstract: Primary care clinicians initiate and oversee colorectal screening for their patients, but colonoscopy, a central component of screening programs, is usually performed by consultants. The accuracy and safety of colonoscopy varies among endoscopists, even those with mainstream training and certification. Therefore, it is a primary care responsibility to choose the best available colonoscopy services. A working group of the National Colorectal Cancer Roundtable identified a set of indicators that primary care cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…However, critiques of the existing screening techniques suggest that these approaches are not infallible but instead depend on histology, location in the colon or rectum, and quality of the endoscopic technique (Baxter et al 2009). Thus, efforts to improve prevention methods, diagnostic capabilities, and subsequent treatment protocols are important to further reducing colorectal cancer mortality (Fletcher et al 2010). The dissemination of effective screening is vital to prevention; moreover, modifiable risk factors have been identified that could lead to further reductions in the risk of developing colorectal cancer and serious sequelae (Joshu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, critiques of the existing screening techniques suggest that these approaches are not infallible but instead depend on histology, location in the colon or rectum, and quality of the endoscopic technique (Baxter et al 2009). Thus, efforts to improve prevention methods, diagnostic capabilities, and subsequent treatment protocols are important to further reducing colorectal cancer mortality (Fletcher et al 2010). The dissemination of effective screening is vital to prevention; moreover, modifiable risk factors have been identified that could lead to further reductions in the risk of developing colorectal cancer and serious sequelae (Joshu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of colonoscopy, conventionally measured based on the completeness and thoroughness of the examination, [26,27], may modify the effectiveness of screening colonoscopy [28,29]. When details of a procedure are not available, some studies consider specialty of the colonoscopist [13,17], a presumed surrogate for quality.…”
Section: Methodological Challenges Facing Studies Of Screening Colonomentioning
confidence: 99%
“…23 The NCCRT has also published guidance for referring clinicians regarding their responsibilities in ensuring that their patients receive quality endoscopy services. 31,32 The CDC and the American Cancer Society also sponsor the International Colorectal Cancer Screening Network, which represents organized CRC screening initiatives from around the world. 33 The network supports quality assurance and program evaluation with the aim of maximizing the benefit and minimizing the risk associated with CRC screening.…”
Section: The Role Of Endoscopists In Public Healthmentioning
confidence: 99%